If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1.5c + 6) + -2c = 24 Reorder the terms: 4(6 + 1.5c) + -2c = 24 (6 * 4 + 1.5c * 4) + -2c = 24 (24 + 6c) + -2c = 24 Combine like terms: 6c + -2c = 4c 24 + 4c = 24 Add '-24' to each side of the equation. 24 + -24 + 4c = 24 + -24 Combine like terms: 24 + -24 = 0 0 + 4c = 24 + -24 4c = 24 + -24 Combine like terms: 24 + -24 = 0 4c = 0 Solving 4c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '4'. c = 0 Simplifying c = 0
| f=2h | | X^3-2x^3-x+2=0 | | 3(x-6)+9=-9 | | 29=5x-2(10-x) | | (2/3)(k-8)=52 | | 9.7y+2.16=11.42 | | y-11=(5/11)(x-10) | | 0.25(16-4x)=7-(1.25x+5) | | x-5y=17fory | | 4g+17=81 | | Xsquared+8x+15=0 | | 73774t+132=11 | | 4(2-3x)-(6x-4)=2(5-5x) | | h=32+48t-16t^2 | | 8n+19=4n+135 | | 2(3.14r)=20 | | 2x+8=25-9x | | 3*(X+2)=15 | | -6.1y=198.25 | | 12c-5c= | | w-16=28 | | 2/3x13 | | 5x^2+21x-4=0 | | -[-[-(6x+5)]]=-(x+5) | | 2(3p-t)-(-4p+t)= | | 24+p=54 | | 0.7r=-91 | | 6-6x=3y | | 11c+1=67 | | A(9+a)=4(2a+5) | | 54v^2+18v-120=0 | | r=f(w+a) |